2014
DOI: 10.1002/ange.201408493
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Anatase: Strong Photocatalytic Dihydrogen Evolution without the Use of a Co‐Catalyst

Abstract: The high-pressure hydrogenation of commercially available anatase or anatase/rutile TiO 2 powder can create a photocatalyst for H 2 evolution that is highly effective and stable without the need for any additional co-catalyst. This activation effect cannot be observed for rutile; however, for anatase/rutile mixtures, a strong synergistic effect can be found (similar to results commonly observed for noble-metal-decorated TiO 2 ). EPR and PL measurements indicated the intrinsic co-catalytic activation of anatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Such features were also observed for high pressure hydrogenated anatase, where they have been identified as a key indicator for establishing intrinsic H 2 evolution ability in TiO 2 [20,21].…”
Section: Hrtem Images Of Reference and H-implanted Nanotubes Are Showmentioning
confidence: 69%
See 3 more Smart Citations
“…Such features were also observed for high pressure hydrogenated anatase, where they have been identified as a key indicator for establishing intrinsic H 2 evolution ability in TiO 2 [20,21].…”
Section: Hrtem Images Of Reference and H-implanted Nanotubes Are Showmentioning
confidence: 69%
“…used directly as a nanoparticle suspension in an aqueous/methanol solution under sunlight (AM 1.5) conditions). The high catalyst activity was attributed to a thin amorphous TiO 2 hydrogenated layer that was formed under high pressure treatment and that encapsulated the anatase core of the nanoparticles, leading to a considerable narrowing of the optical absorption band-gap of the treated material (turning its appearance to black).Follow-up work mainly replaced the high pressure treatment by various other reductive treatments (high temperature Ar/H 2 , Ar, vacuum exposure, or electrochemical reduction, etc.[12-16]) -such material was reported to cause a similar effect on the Pt-co-catalyzed photocatalytic H 2 -production or when used in a range of other electrochemical applications [17][18][19].More recently, we reported that high pressure/high temperature/hydrogen-treated TiO 2 (HPTTiO 2 ) in form of nanotubes [20] and powder [21] shows another key feature, that is, a strongly enhanced photocatalytic activity for hydrogen production in absence of any noble metal cocatalyst [22]. The work thus showed that a HPT-treatment not only leads to the effects observed by Chen and Mao, but additionally suggested that a co-catalytic center in TiO 2 is formed -similar in its effect to noble metal decoration.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that anatase is active in both catalysis and photocatalysis, and is the most used polymorph of TiO 2 . 15,46,51,52 Although several factors such as facets and surface areas have been considered to contribute to the high activity of anatase, 53 the type and activity of surface OH groups might also play a critical role. The present work demonstrated that the crystal phase of TiO 2 determines the nature of the surface OH groups, which then determines the reaction of NO 2 on TiO 2 .…”
Section: Discussionmentioning
confidence: 99%